Towards markerless navigation for percutaneous needle insertions - Seitel, Alexander; Bellemann, Nadine; Hafezi, Mohammadreza; Franz, Alfred Michael; Servatius, Mark; Saffari, Arash; Kilgus, Thomas; Schlemmer, Heinz-Peter; Mehrabi, Arianeb; Radeleff, Boris; Maier-Hein, Lena (International journal of computer assisted radiology and surgery, 2016)
Percutaneous needle insertions are increasingly used for diagnosis and treatment of abdominal lesions. The challenging part of computed tomography (CT)-guided punctures is the transfer of the insertion trajectory planned in the CT image to the patient. Conventionally, this often results in several needle repositionings and control CT scans. To address this issue, several navigation systems for percutaneous needle insertions have been presented; however, none of them has thus far become widely accepted in clinical routine. Their benefit for the patient could not exceed the additional higher costs and the increased complexity in terms of bulky tracking systems and specialized markers for registration and tracking.